Complete elimination of hyperleukocytosis risk in AML through early high-quality disease remission - Lyu, Guoqing; Lyu, Wenting (Frontiers in Oncology, 2024)
Background Acute myeloid leukemia (AML) with hyperleukocytosis (HL) is a severe medical emergency associated with high mortality rates and poor prognosis. Prompt and urgent treatment is crucial to address this medical emergency. This study aims to elucidate appropriate diagnostic thresholds for HL and investigate underlying mechanisms and potential targeted therapies. Methods X-tile software was employed to analyze white blood cell (WBC) count thresholds in AML patients using data from TCGA and TARGET AML databases. METASCAPE and Gene Set Enrichment Analysis (GSEA) were conducted to explore the molecular mechanisms underlying HL in AML. Potential molecular targeted drugs were identified using the CELLMINER platform. Results Analysis revealed that a WBC count threshold of 75×109/L, rather than the conventional 100×109/L, is more appropriate for diagnosing HL in adult AML patients. This revised threshold could aid clinicians in identifying a greater number of patients requiring immediate intervention. Significant correlations were observed between HL and specific mutations, including NPM1, FLT3, and DNMT3A. For pediatric AML patients, the HL threshold was determined to be 165×109/L. Achieving complete remission (CR) or deeper levels of remission significantly reduces the risks associated with HL. The reduction in risk can lead to survival outcomes for HL patients that are comparable to those of non-hyperleukocytosis patients. Differential gene expression analysis indicated that downregulation of cell adhesion molecules is implicated in HL pathogenesis. Potential targeted therapies for AML with HL include Bcl2 inhibitors and histone deacetylase inhibitors. Clinical observations demonstrated that the addition of Bcl2 inhibitors, such as Venetoclax, to standard therapy results in a rapid reduction in WBC counts, thereby reducing tumor burden and providing prompt symptom relief. Combining these targeted drugs with conventional therapies appears promising in mitigating risks associated with HL. Conclusions Lower diagnostic thresholds for HL in AML, identifies critical genetic correlations, and highlights effective molecular targeted therapies. Proactive early treatment is crucial for achieving deep remission and reducing HL risk. Future therapeutic strategies should consider integrating molecular targeted drugs with conventional therapies to improve outcomes for patients facing this high-risk hematological emergency.